High Performance Imaging through Occlusion via Energy Minimization-Based Optimal Camera Selection. (22nd November 2013) - Yang, Tao; Zhang, Yanning; Tong, Xiaomin; Ma, Wenguang; Yu, Rui
Seeing an object in a cluttered scene with severe occlusion is a significantly challenging task for many computer vision applications. Although camera array synthetic aperture imaging has proven to be an effective way for occluded object imaging, its imaging quality is often significantly decreased by the shadows of the foreground occluder. To overcome this problem, some recent research has been presented to label the foreground occluder via object segmentation or 3D reconstruction. However, these methods usually fail in the case of complicated occluder or severe occlusion. In this paper, we present a novel optimal camera selection algorithm to handle the problem above. Firstly, in contrast to the traditional synthetic aperture photography methods, we formulate the occluded object imaging as a problem of visible light ray selection from the optimal camera view. To the best of our knowledge, this is the first time to "mosaic" a high quality occluded object image via selecting multi-view optimal visible light rays from a camera array or a single moving camera. Secondly, a greedy optimization framework is presented to propagate the visibility information among various depth focus planes. Thirdly, a multiple label energy minimization formulation is designed in each plane to select the optimal camera view. The energy is estimated in the 3D synthetic aperture image volume and integrates the multiple view intensity consistency, previous visibility property and camera view smoothness, which is minimized via graph cuts. Finally, we compare this approach with the traditional synthetic aperture imaging algorithms on UCSD light field datasets and our own datasets captured in indoor and outdoor environment, and extensive experimental results demonstrate the effectiveness and superiority of our approach.